Retrospective cohort study to determine the effect of preinjury antiplatelet or anticoagulant therapy on mortality in patients with major trauma - Yamaji, Fuminori; Okada, Hideshi; Kamidani, Ryo; Kawasaki, Yuki; Yoshimura, Genki; Mizuno, Yosuke; Kitagawa, Yuichiro; Fukuta, Tetsuya; Ishihara, Takuma; Suzuki, Kodai; Miyake, Takahito; Kanda, Norihide; et al. (Frontiers in Medicine, 2023)
Objective This study aimed to compare outcomes among patients who sustained major trauma from injury with and without receiving antiplatelet therapy (APT) or anticoagulant therapy (ACT) to test the hypothesis that APT does not increase the risk of mortality. However, ACT increases the mortality risk in the acute phase of trauma. Methods Patients registered in the Japanese Observational body for Coagulation and Thrombolysis in Early Trauma 2 between April 2017 and March 2018 who had sustained a severe injury in any anatomic region of the body, as determined using an injury severity score (ISS) ≥ 16 were included in this retrospective cohort study. We analyzed the mortality within 24 h from the arrival using a multivariable linear regression analysis adjusted for several confounding variables. Results We identified 1,186 eligible participants who met the inclusion criteria for this study: 105 in the APT (cases), 1,081 in the non-antiplatelet therapy (nAPT) group (controls), 65 in the ACT (cases), and 1,121 in the non-anticoagulant therapy (nACT) group (controls). The mortality within 24 h in the ACT group was significantly higher than in the nACT group (odds ratio 4.5; 95%CI: 1.2–16.79; p = 0.025); however, there was no significant difference between the two groups with or without the antiplatelet drug (odds ratio 0.32; 95%CI: 0.04–2.79; p = 0.3) administration. Other outcomes, like the 28-day mortality, mortality at discharge, and surgery for hemostasis, were not significantly different between regular users and non-users of either antiplatelet or anticoagulant drugs. Conclusion Regular antiplatelet medications did not increase mortality within 24 h, 28 days, or at discharge in patients with major trauma, suggesting that standard treatment, including surgery, is sufficient.